Respuesta :

Answer:

x= -11

Step-by-step explanation:

You would distribute the 2 to x and 3 which would make the equation 2x+6=-16. next, you would subtract 6 from both sides making it 2x=-22. you would then divide both sides by 2 to get x=-11

Answer:

x = -11

Step-by-step explanation:

I decided to start off by thinking, "What number multiplied by 2 equals -16?"

In this case, -8 would be the answer to that question.

Then, I solved the equation x + 3 = -8.

In this case, x would equal -11.

To check my answer, I solved the equation with x as -11.

-11 + 3 = -8, multiplied by 2, which equals -16.

Hope this helps.